Systematic Analysis of Coronavirus Disease 2019 (COVID-19) Receptor ACE2 in Malignant Tumors: Pan-Cancer Analysis - Song, Jukun; Han, Jing; Liu, Feng; Chen, Xianlin; Qian, Shenqi; Wang, Yadong; Jia, Zhenyu; Duan, Xiaofeng; Zhang, Xiangyan; Zhu, Jianguo (Frontiers in Molecular Biosciences, 2020)
Background: Coronavirus disease 2019 (COVID-19) was first detected in patients with pneumonia in December of 2019 in humans. Nowadays, Several observational studies reported that cancer has been identified as risk factor for COVID-19. However, systematic analysis of ACE2 in malignant tumors remained to be elucidated. To address this issue, we conducted systematic analysis of ACE2 expression profiles across 33 types of tumors. Methods: The distribution of ACE2 expression was analyzed via the GTEx, CCLE, TCGA pan-cancer database. We evaluated the inﬂuence of ACE2 on clinical prognosis using Kaplan-Meier survival plot and COX regression analysis. The correlations between ACE2 and cancer immune inﬁltrates was investigated in various cancer. Meanwhile, the relationship between ACE2 and immune neoantigen, TMB, microsatellite instability, mismatch repair genes (MMRs), HLA genes and DNA methyltransferase (DNMT) was also explored. Gene mutation frequency in various tumor samples was analyzed based on the ACE2. Using the GSEA methods, the functional enrichment analysis was also conducted in various cancer. Results: The GTEx dataset was used to analyze the distribution of ACE2 in normal tissues, and we observed that the ACE2 was almost expressed in 31 tissues. For further analysis, we downloaded the data of each tumor cell line from the CCLE database, and the results indicated that the expression level of ACE2 in various organs of cancer cells showed low to medium expression. Although the aberrantly expressed was observed in most of cancer, high expression of ACE2 was not linked with OS, DFS, RFS and DFI in majority of tumors in TCGA pan-cancer data. We found that ACE2 expression was significantly correlated with inﬁltrating levels of Macrophages and Dendritic cells, CD4+ T cells, CD8+ T cells, and B cells in multiple of tumors. Positive relationship between gene expression and immune neoantigen, TMB, microsatellite instability was also detected in multiple of cancers. In order to observe the effect of ACE2 on tumors, the GSEA analysis revealed that several cancer-associated pathways and immune-related pathways were hyperactivated in the higher ACE2 group in most of tumors. Conclusions: These ﬁndings suggest that ACE2 is not correlated with prognosis in most of cancer.